2021
DOI: 10.3390/pathogens10060646
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Variation in Coxiella burnetii Seroprevalence in Dairy Farms Located in South-Western Ethiopia: Understanding the Broader Community Risk

Abstract: Q fever is a zoonotic disease that is caused by Coxiella burnetii and leads to abortion and infertility in ruminants and debilitating disease in humans. Jimma zone, including Jimma town, located in the Oromia region of Ethiopia, was affected by an outbreak of abortions in ruminants related to Q fever infection between 2013 and 2015. This study aimed to investigate the geo-clustering of C. burnetii seroprevalence in dairy farms of Jimma town and identify the environmental risk factors associated with seropreval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The current study reports an overall seroprevalence of 18.77% (95% CI, 17.59–19.99%) with varying levels from the tested livestock species of various locations in Ethiopia. Our finding is in a close similarity with the 20% prevalence reported from south-western Ethiopia using similar serological methods [ 23 ]. However, it is lower than those reported by Gumi et al [ 13 ] and Tesfaye et al [ 24 ] who estimated a prevalence of 31.6% and 28.46%, respectively, in other parts of Ethiopia.…”
Section: Discussionsupporting
confidence: 91%
“…The current study reports an overall seroprevalence of 18.77% (95% CI, 17.59–19.99%) with varying levels from the tested livestock species of various locations in Ethiopia. Our finding is in a close similarity with the 20% prevalence reported from south-western Ethiopia using similar serological methods [ 23 ]. However, it is lower than those reported by Gumi et al [ 13 ] and Tesfaye et al [ 24 ] who estimated a prevalence of 31.6% and 28.46%, respectively, in other parts of Ethiopia.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, a recent cross-sectional study in India reported that age is the paramount multivariable risk factor of Q fever exposure in dairy cattle [68]. Increasing exposure rates as animals get older is consistent with an endemic situation with circulation of the pathogen and increasing likelihood of exposure to the pathogen and its reservoirs such as other infected hosts, natural reservoirs, and/or environmental sources the longer the animal lives [3,10,23,67,69].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from domestic ruminants, other reservoirs like ticks may have a role as potential arthropod vectors and in the dispersal the pathogen through biting and environmental contamination [17][18][19]. The bacterium can survive harsh conditions and attach to dust in the environment and finally be transported over long distances (to more than 10 km) via the wind [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the country’s agrarian nature, where a large proportion of the population depends on livestock farming, the risk of transmission from animals to humans is relatively high. 14 , 41 Furthermore, Ethiopia faces challenges in terms of healthcare infrastructure and access to proper diagnostic and treatment facilities in rural areas, which may impede early detection and effective management of the C. burnetii infection. Moreover, factors like climate change, changing agricultural practices, and population movement could also influence the prevalence and distribution of the disease in Ethiopia.…”
Section: Burnetii Infection: Challenges Control and Its Stat...mentioning
confidence: 99%